Maternal food diversity and seasonality as conditions for children's nutritional status: an integrative review (Revista Contexto & Saúde, 2025)
Nutritional status is a determining factor in achieving good health. The aim of the study was to evaluate whether maternal dietary patterns can influence nutritional disorders in children under two years of age. An integrative review was carried out, with data collected from the following databases: EMBASE, PubMed, LILACS and SciELO. A total of 273 studies were identified, 11 of which answered the guiding question, and only four met all the inclusion criteria. The findings showed that maternal nutrition decreased the risk of nutritional disorders in children. Maternal dietary diversity was a protective factor for stunting in children and a predictor of children's food variety, consequently influencing their food consumption. Maternal abstinence from food is among the common factors related to child malnutrition. It can be concluded that maternal nutrition is a protective factor for the development of nutritional disorders in children between zero and 24 months of age, since mothers are usually responsible for feeding the family, especially in traditional societies.
Keywords: maternal nutrition; eating behaviour; infant nutritional disorders